Progression of Large Vessel Disease in Patients With Giant Cell Arteritis–Associated Ischemic Stroke: The Role of Vascular Imaging: A Case Series. Issue 8 (24th December 2021) - Guisado-Alonso, Daniel; Edo, M. Carmen; Estrada Alarcón, Paula Valentina; García-Sánchez, Sonia María; Font, Maria Àngels; Mena Romo, Luis; Marrero-González, Paula; Mengual, Juan José; Castrillo, Laura; Montull, Caterina; Corominas, Hector; Gómez-Choco, Manuel
Abstract : Objective: Giant cell arteritis (GCA) can cause ischemic stroke (IS) due to the involvement of the internal carotid and vertebral arteries. The aim of our study is to describe the pattern of stroke recurrence in patients with GCA-related IS and the role of vascular imaging in the follow-up of these patients. Methods: We conducted an observational study of 2417 consecutive patients diagnosed with IS and admitted to our hospital from January 2012 to December 2018. We reviewed patients with GCA-related IS and the relationship of erythrocyte sedimentation rate, C-reactive protein, vascular status, and clinical course. Results: We found 4 patients with GCA-related IS among 2417 IS patients: 1 woman (25%); median age, 77.3 years (67–85 years). Mean follow-up was 3.6 years. Initial vascular workup showed vertebral artery stenosis in all of them and internal carotid artery stenosis in 2 patients. All patients were started on treatment with full-dose prednisone, associated with methotrexate in 2 cases. Follow-up color-coded duplex sonography disclosed progression of arterial stenoses in 3 patients who suffered a recurrent IS (days after index stroke; mean, 27.67 [SD, 10.97]) despite normal C-reactive protein and erythrocyte sedimentation rate values. Conclusions: Vascular imaging, especially with color-coded duplex sonography, could play a role in the follow-up of patients with GCA-related IS and identify those patients with higher risk of recurrent stroke.